Anecdotes on Dr Movius’ Paper: Champion de Crespigny and Reiss/Avigad - Wolff, Samuel R.; Brandl, Baruch; Franklin, Norma (Buried History: The Journal of the Australian Institute of Archaeology, 2024)
This note supplements Geoffrey Movius’ paper about Nancy Champion de Crespigny Movius that appeared in the previous issue of Buried History. Some anecdotes are presented, especially as they relate to her participation in the excavations at Samaria in 1933. It is suggested that the person tentatively identified as Eliezer Sukenik in the staff photograph is in fact Nahman Reiss, later to become Nahman Avigad. Reiss’s role in the excavations at Samaria is finally commented upon.